Enhancement of Xanthate Adsorption on Cerussite Surfaces by Pb(II) Activation and Its Effect on Floatability - Yongchao Miao; Shuming Wen; Zhihao Shen; Qian Zhang; Qicheng Feng (Molecules, 2023)
Cerussite is a lead oxide mineral resource that is typically enriched through sulfidization flotation. The surface sulfidation degree and the high solubility of cerussite strongly affect the flotation ability of cerussite. In the current work, lead ions were used to pretreat cerussite to intensify its sulfidization flotation. The sulfidization mechanism regulating the lead ions pretreatment on cerussite was investigated by the micro-flotation test, ToF-SIMS, zeta potential measurement, adsorption test, and XPS. The results from the micro-flotation test demonstrated that the floatability of cerussite could be improved by adding an appropriate amount of lead ions. Compared with the treatment involving only Na2S, the maximum recovery increased by 17.57%. Adsorption experiments showed that lead modification improved the stability of xanthate products on the surface of cerussite. According to the measurement of zeta potential and the results of ToF-SIMS, the addition of lead ion Pb pretreatment increased the number of active Pb sites adsorbed by xanthate, thereby improving the formation of hydrophobic Pb-dilute precipitate. Therefore, the interaction between lead ions and the surface of cerussite enhances the strength and stability of the hydrophobic layer, resulting in enhanced hydrophobicity of cerussite.